Relationships between maximum tongue pressure and second formant transition in speakers with different types of dysarthria. - Toshiaki Tamura; Yasuhiro Tanaka; Yoshihiro Watanabe; Katsuro Sato (PLoS ONE)
The effects of muscle weakness on speech are currently not fully known. We investigated the relationships between maximum tongue pressure and second formant transition in adults with different types of dysarthria. It focused on the slope in the second formant transition because it reflects the tongue velocity during articulation. Sixty-three Japanese speakers with dysarthria (median age, 68 years; interquartile range, 58-77 years; 44 men and 19 women) admitted to acute and convalescent hospitals were included. Thirty neurologically normal speakers aged 19-85 years (median age, 22 years; interquartile range, 21.0-23.8 years; 14 men and 16 women) were also included. The relationship between the maximum tongue pressure and speech function was evaluated using correlation analysis in the dysarthria group. Speech intelligibility, the oral diadochokinesis rate, and the second formant slope were based on the impaired speech index. More than half of the speakers had mild to moderate dysarthria. Speakers with dysarthria showed significantly lower maximum tongue pressure, speech intelligibility, oral diadochokinesis rate, and second formant slope than neurologically normal speakers. Only the second formant slope was significantly correlated with the maximum tongue pressure (r = 0.368, p = 0.003). The relationship between the second formant slope and maximum tongue pressure showed a similar correlation in the analysis of subgroups divided by sex. The oral diadochokinesis rate, which is related to the speed of articulation, is affected by voice on/off, mandibular opening/closing, and range of motion. In contrast, the second formant slope was less affected by these factors. These results suggest that the maximum isometric tongue strength is associated with tongue movement speed during articulation.